Cultures and societies in a changing world - Griswold, Wendy (Sociology for a new century., 2013)
In the Fourth Edition of Cultures and Societies in a Changing World, author Wendy Griswold illuminates how culture shapes our social world and how society shapes culture. Through this book, students will gain an understanding of the sociology of culture and explore stories, beliefs, media, ideas, art, religious practices, fashions, and rituals from a sociological perspective. Cultural examples from multiple countries and time periods will broaden students' global understanding. Students will develop a deeper appreciation of culture and society from this text.